Early Childhood Islamic Boarding School in The Perspective of Education Sciences - Maesaroh Lubis; Darliana Sormin; Wael 'Ali Sayyed; Abdulroman Mahir (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the fast growth of early childhood Islamic boarding schools (children of 5-7 years old). One of the reasons for the fast growth of Islamic boarding schools is the high public interest caused by the reduced trust of parents in modern educational institutions. This study used a qualitative literature review method with a systematic review approach. Data collection was carried out using an online reference search by entering the keyword